Freedom of Information Access : Key Challenges, Lessons Learned and Strategies for Effective Implementation - World Bank (World Bank, Washington, DC, 2020)
Implementation of the right to information as established in a Freedom of Information Access (FOIA) Law provides a foundation for institutionalization of transparency and support for anti-corruption efforts. Passage of a FOIA law is only a first step toward accessibility of data and documents held by public agencies, however. Effective implementation of a FOIA requires that public agencies take additional steps to put laws into practice and overcome common implementation challenges that can render FOIA laws ineffective. This note, which builds on previous World Bank research on factors determining effective implementation of FOIA laws, reviews cases of introduction of FOIA laws around the world and summarizes the main challenges, lessons learned and key strategies emerging from these experiences. Its primary aim is to inform Italian public agencies charged with implementation of the FOIA law about steps they can take toward effective implementation. As such, it focuses on areas of activity typically within the purview of public agencies, as opposed to those typically in scope of policymakers or central agencies charged with implementation and/or legislative oversight of FOIA.